Caracterización de la pectina obtenida de la piel de la pitahaya amarilla (Hylocereus megalanthus) - Águila Vera, Paúl Clemente (2018)
The objective of this research project is to characterize the pectin extracted from the skin of the yellow pitahaya (Hylocereus megalanthus), from the Palora canton of the Procel farm. The analyzes were carried out in the City of Guaranda, Sector Laguacoto II, Laboratories of the Research Department of the State University of Bolívar, Agroindustrial Engineering Career. After the physical analyzes of the pectins obtained from yellow pitahaya in different stages of maturity and type of acid used in this study, the pH values of both the pectin obtained from T1 (Pitahaya green + citric acid) and T2 (green + acid) hydrochloric) were quite similar from 3.3 to 3.4 respectively, in the same way as for T3 (green pitahaya + citric acid) and T4 (ripe pitahaya + hydrochloric acid) were similar from 4.6 to 4.9 respectively. In the content of humidity and ash, a percentage of 9.6 and 5.4 was obtained regarding T1; of 8.4 and 5.0 for T2; 9.2 and 5.4 for T3: 9.7 and 5.7 regarding T4. In the chemical analyzes, the percentage of the degree of esterification of the pectin obtained from (T1) was 44.4% which indicates that it is a low methoxyl pectin, while the pectins obtained from the treatments (T2, T3, and T4) the percentage of esterification was more than 50.7% which indicates that these pectins are high methoxyl. The protein content of each of the treatments was; T1 (4.7%), T2 (7.1%), T3 (5.8%), T4 (5.2%) respectively, when determining the percentage of Galacturonic anhydride acid (% AAG) which allows to know the degree of purity of the pectic substance; the results were similar for each of the 35% purity treatments of the pectic substance. The Transmittance analyzes in the pectin of yellow pitahaya skin; Green and mature state clearly shows the presence of functional groups characteristic of a pectin; at the wavelength (λ) of 3279 the band corresponding to the -OH functional group is found, for the yellow green pitahaya skin pectin while the same group is evidenced in the mature pectin at a λ of 3336; for λ 2918 and 2920 is the band corresponding to the aliphatic C-H bond in both pectins; in the λ of 1734 is found the band corresponding to the C = O esterified carbonyl group corresponding to the yellow green pitahaya skin pectin, while the same carbonyl group for mature pectin is found in the λ of 1731; in the λ of 1615 and 1629 is the band corresponding to the group of total carbonyls in each of the pectins respectively and in a λ of 1014 and 1015 is the band corresponding to the vibration of the -CO bond of each of the pectins. With all these results, it is concluded that the pitahaya skin pectin in green state plus the use of hydrochloric acid, is the best according to the analyzes performed, adjusting to all the established parameters, it is also the first time that pectin is extracted from the yellow pitahaya eco-type called "Palora" which is a pitahaya endemic to the Ecuadorian East, which is cultivated in the Palora canton, Morona Santiago province